Estudo comparativo entre anestesia espinhal com lidocaína e bupivacaína em Tartaruga-da-Amazonia (Podocnemis expansa Schweigger) (Testudines, Podocnemididae) - Nascimento, Liliane Rangel (2013)
Was aimed at evaluating the effects of lidocaine and bupivacaine via the spine in turtles of the species Podocnemis expansa in promoting motor and sensitive blockages in the tail/cloaca and pelvic members, as well as the existence of significant differences in the effects produced by the two drugs. Was used 20 animals with average weights of 1.15 kg, which were divided into two anesthetic protocols: 4.6 mg/kg of lidocaine 2% and 1.15 mg/kg of bupivacaine 0.5% deposited in the spinal region in the sacro-coccigeal area. Was evaluated the latency period, the reasonable period for anesthesia and the recovery period. For the latency period of the tail/cloaca we obtained (Lca) 54±34.05 seconds (sec) and 54±18.97sec as mean values for lidocaine and bupivacaine respectively. The latency period of the pelvic member (LMp) was in average 264±75.89 seconds for lidocaine and 180±126.49 sec for bupivacaine. Then the reasonable period for anesthesia on the tail/cloaca (Hca) was 36±9.43 minutes (min) and 60.8±32.10 min for the anesthetics in the same sequence. The averages for the reasonable period in pelvic members (HMp) were 24.6±10.83 min and 58.7±33.82 min for the respective drugs. Finally, the recovery period (Rec) was 33.5±16.33 min for lidocaine and 77.5±33.27 min for bupivacaine. The average times found for bupivacaine were significantly higher except during periods of latency of the tail/cloaca and pelvic members. The heart rate remained within the range considered normal for the testudines. Was conclude that the use of lidocaine and bupivacaine via the spine is safe and effective in the promotion of anesthesia in the region of the tail/cloaca and in pelvic limbs, and that the reasonable times for anesthesia are enough to perform simple and ordinary surgical procedures.